2006
DOI: 10.1148/radiol.2391050073
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebroplasty: Relationship between Vertebral Body Bone Marrow Edema Pattern on MR Images and Initial Clinical Response

Abstract: PVP resulted in significantly greater clinical improvement in patients with an extensive bone marrow edema pattern than in those without this pattern. (c) RSNA, 2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…Imaging procedures such as magnetic resonance (MR) imaging, bone scintigraphy, and computed tomography (CT) help determine the treatment location (5). Of these procedures, MR imaging is most favored because of its ability to provide information on both anatomic vertebral collapse and edema (1,6,7).…”
Section: Patientsmentioning
confidence: 99%
“…Imaging procedures such as magnetic resonance (MR) imaging, bone scintigraphy, and computed tomography (CT) help determine the treatment location (5). Of these procedures, MR imaging is most favored because of its ability to provide information on both anatomic vertebral collapse and edema (1,6,7).…”
Section: Patientsmentioning
confidence: 99%
“…In all these cases, consensus was obtained without difficulties by authors 1 and 5. A total of 60 papers were excluded after review; 27 as they dealt with specific LBP conditions ( Table 2) and 33 for other reasons: one review article [55], four case reports [7,27,129,148], one double publication [90], one of two studies reporting data from the same study sample [80], ten for evaluating signal changes other than those related to the endplate [6,20,51,53,71,113,116,139,146,150], and eight articles because they did not report the exact numbers needed to calculate the prevalence rates of VESC [4,10,109,110,114,122,133,141]. Finally, eight articles were excluded because the study samples were selected on the basis of the presence of VESC [41, 50,56,63,68,134,137,149].…”
Section: Review Processmentioning
confidence: 99%
“…There was no difference in the prevalence rates of VESC in relation to sex in the 45 study samples that reported the Schmorl's nodes [60,94,135] Fracture [139,151] Spinal cord infarction [157] Other conditions [42, 121] prevalence in individuals or in the 22 study samples that reported the prevalence in relation to levels (data not shown).…”
Section: Sexmentioning
confidence: 99%
“…3,4 Among these procedures, MRI is the modality of choice to obtain information about both vertebral fractures and bone marrow oedema. [5][6][7][8] However, MRI is not routinely used in all patients with vertebral trauma owing to reduced availability, contraindications and/or metal artefacts. Compared with MRI, CT is more available, requires less time and has better spatial resolution.…”
Section: Introductionmentioning
confidence: 99%